Evaluating the Influence of Different Recommended Dietary Levels of Cu and Zn on Finishing Pigs - Li, Meijun; Tang, Wei; Liao, Peng; Li, Yunhu (Frontiers in Veterinary Science, 2022)
This study was conducted to evaluate the effects of dietary supplementation of different recommended levels of Cu and Zn on antioxidant capacity, tissue mineral status, minerals excretion, meat quality, digestive enzyme activity, and metal transporters in finishing pigs. One hundred twenty pigs were randomly divided into fourtreatments:1)basal diet without added Cu or Zn (control), 2) basal diet + 35 mg of supplemental Cu/kg from cupreous N-carbamylglutamate chelate (NCG-Cu) + 150 mg of supplemental Zn/kg from zinc-methionine chelate (Zn-Met) (AC), 3)basal diet + 3.0 mg of supplemental Cu/kg from NCG-Cu + 43 mg of supplemental Zn/kg from Zn-Met (CN), and 4) basal diet + 3.5 mg of supplemental Cu/kg from NCG-Cu + 50 mg of supplemental Zn/kg from Zn-Met (NRC100). Pig growth performance was not affected by the level of Cu or Zn. Among the four treatments, the AC treatment had the highest level (P < 0.05) of glutathione peroxidase (GSH-Px). Pigs fed the AC diet had the highest (P< 0.05) liver Zn, fecal Cu, and fecal Zn among the four treatments. The protein levels of trypsin and aminopeptidase N (APN) in the intestinal mucosa showed their highest levels (P < 0.05) in the NRC100 and AC treatments. The mRNA levels of trypsinogen and APN were significantly up-regulated (P < 0.05) in the AC, CN, and NRC100 treatments compared with the control. The mRNA levels for the Zn transporter genes SLC30A1 (ZnT1) and SLC30A2 (ZnT2) were significantly up-regulated (P< 0.05) in the AC treatment, and the mRNA levels for SLC39A4 (ZIP4) and metallothionein 1 (MT) in the AC, CN, and NRC100 treatments were significantly up-regulated (P< 0.05) compared with the control. Meat quality (i.e., carcass weight, backfat thickness, loin muscle area, pH, color traits, marbling, and shear force) were not affected (P> 0.05) by the different recommended levels of Cu and Zn. These results indicated that the supplemental Cu and Zn levels routinely used in AC diets in Chinese commercial feed enterprises should be reduced, although AC diets can increase antioxidant capacity, digestive enzyme activity, and metal transporter gene expression in finishing pigs.